Enhancing Science Process Skills through Project-Based Learning Collaboration on Soft Cheese-Making Practicum Using Local Coagulants - Sudirman Sudirman (Postgraduate, University of Mataram, 2025)
Despite the recognized benefits of project-based learning (PjBL), there remains a need to empirically investigate how collaboration within PjBL frameworks, especially when leveraging local resources, impacts the development of science process skills in practicum settings. This study examines whether collaborative project‑based learning (PjBL) using locally available coagulants enhances high‑school students’ science process skills (SPS) in a soft cheese‑making practicum. This study used A quasi‑experimental, one‑group pretest–posttest design was implemented with secondary students enrolled in a practicum course (N = 30). SPS were assessed with a validated rubric covering observing, following instructions, recording data, classifying, predicting, inferring, and conducting investigations. Paired t‑tests evaluated pre–post changes; significance was set at p < 0.05, posttest means ranged from 3.27 to 3.72 on a 4‑point scale. All SPS indicators showed statistically significant pre–post improvement (paired t range ≈ 13.87–15.06; p < 0.001), indicating that collaborative PjBL contextualized with Calotropis gigantea and Solanum indicum supports SPS development in low‑resource laboratory settings. Implementing collaborative PjBL leveraging local coagulants showed improvements in students’ SPS within the practicum. Because no control group was analyzed, claims of comparative superiority over traditional methods are not warranted; future studies should include a control group and independent‑samples tests on gain scores.